Relatório de Estágio Profissional "Gostar do que se faz é essencial para o sucesso: o percurso de uma estudante-estagiária" - Patrizia Nunes Leal (2018)
The present practicum report arises in the ambit of the curriculum unit School Placement, which is an integral part of the study plan of the 2nd cycle of studies leading to the degree of Master of Teaching Physical Education in the Basic and Secondary Education, from the Faculty of Sport of the University of Porto. This practicum was carried out in a school located in Castêlo da Maia, which practicum center consisted of three trainee students, a mentoring teacher and a cooperating teacher who helped us on this journey. This document presents the most relevant moments of a student-trainee (the author) of a year full of learning and challenges, as well as the difficulties overcome and the knowledge acquired. In terms of structure, the document begins with an introduction, which presents a conceptual framework of the practicum in the context of initial education, a characterization of the practicum and its objectives, the purpose and the process of carrying out the report. After this component the document it organized into five chapters: 1) Personal Framing - where I present an autobiographical reflection, a personal analysis of my skills and weaknesses, the initial expectations for the practicum year and the impact with reality; 2) Professional Practice Framework - materializes the legal, institutional and functional framework of practicum; 3) Professional Practice - englobes the three performance areas provided for the professional practicum regulations: Organization and management of teaching and learning; Participation in School and Community Relations; Professional development. 4) Research study developed during the second and third periods, in which it was sought to verify the effect of the regular application of the functional training to the level of the physical fitness of the students, aiming also to increase the knowledge about the processes of development and maintenance of the physical condition; 5) Conclusions and perspectives for the future - where I present the most relevant learning acquired and future aspirations.